'See no evil': towards an analytics of Europe's legal borderlands. Issue 1 (March 2022) - Franko, Katja
Abstract: This article argues that spatial exclusion is a central element of, and a precondition for, exclusion from fundamental rights. Keeping individuals who are seeking access to rights geographically separated from spaces ordered by the rule of law is a defining feature of the contemporary European legal order. The European legal space is surrounded by borderlands, which are not only humanitarian borderlands, but also legal borderlands. Unpacking the meaning of borderlands and frontier zones could, therefore, be greatly productive for future perspectives on legal geography.